The Orthodox Neo-Patristic Movement’s Encounter with the Christian “Other”: An Ecumenical Hermeneutics of Receptivity - Coman, Viorel ca. 20./21. Jh. (Theological studies, 2020)
This article discerns an ecumenical hermeneutics of receptivity towards Western theology in the writings of the Orthodox Neo-patristic author Dumitru Stăniloae (1903–1993). In so doing, the article shows that, despite its rejection of Western scholasticism, the program of the Orthodox Neo-patristic movement also included an ecumenical component which, instead of cultivating opposition between Eastern and Western Christianity, invited churches to dialogue and mutual enrichment. The exploration of Stăniloae’s notion of “open sobornicity” is the main focus of this article.